2021
DOI: 10.1111/jocn.15690
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ experiences of caring for women’s emotional and mental well‐being during pregnancy

Abstract: Aims and Objectives To explore midwives’ experiences of caring for women's emotional and mental well‐being during pregnancy. Background Transitioning to motherhood is a major life event for any woman and while it is a joyful experience for the majority, 15%–25% of women will experience a perinatal mental health problem. Providing psychological support to mothers by midwives is acknowledged internationally. The 2016 Irish National Maternity Strategy identifies midwives as being ideally placed to assess women's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(90 reference statements)
2
8
0
Order By: Relevance
“…Our findings on security and work experience are supported by, among other things, the study by Fontein-Kuipers et al (35) in which midwives cited work experience as their most important source of knowledge when it came to mental health. This is consistent with Fletcher et al (9), who also found a clear connection between work experience and midwives' self-confidence, as well as their ability to detect and deal with women with antenatal depression. This is also supported by Ross-Davie et al's (36) study which concluded that midwives felt that their education prepared them too little for addressing mental health versus physical health in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings on security and work experience are supported by, among other things, the study by Fontein-Kuipers et al (35) in which midwives cited work experience as their most important source of knowledge when it came to mental health. This is consistent with Fletcher et al (9), who also found a clear connection between work experience and midwives' self-confidence, as well as their ability to detect and deal with women with antenatal depression. This is also supported by Ross-Davie et al's (36) study which concluded that midwives felt that their education prepared them too little for addressing mental health versus physical health in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Lack of time is often reported as a problem when it comes to addressing mental health (28). Several studies show that a lack of time can prevent sensitive topics from being addressed (9,10,34) which was also confirmed by the midwives in our study. Higgins et al suggest that role-playing games and digital tools can be used to develop midwives 'skills in opening up conversations, as it is challenging to bring up sensitive topics in a short time and at the first meeting with a patient (10,34).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings suggest that this can only occur when the midwife can base support on both professional knowledge about the transitional process (education) and the experiential knowledge of the woman [5, 49]. The midwife also has to regard maternal emotional health as equally important as physical health [8, 53–55]. Our findings also show that the midwife needs to be empathic and emotionally mature to provide support to women in adapting to the maternal role and identity during and after pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…Non-pharmacological interventions developed specifically for pregnant women with anxiety symptoms are promising, although interventions have not been evaluated in definitive trials 21–26. In England, midwives provide care for all women throughout pregnancy, thus midwives are ideally situated to identify mental health concerns and support women’s emotional and psychological well-being 20 27 28…”
Section: Introductionmentioning
confidence: 99%